The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/hlca.19830660622
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of Thiosulfate in Semiconductor Dispersions

Abstract: SummaryConduction band electrons produced by band gap excitation of Ti0,-particles reduce efficiently thiosulfate to sulfide and sulfite.2 e$ (Ti02)+ S20$----+ S2-+ SO:-This reaction is confirmed by electrochemical investigations with polycrystalline Ti02-electrodes. The valence band process in alkaline Ti02-dispersions involves oxidation of S20$-to tetrathionate which quantitatively dismutates into sulfite and thiosulfate, the net reaction being: 2h+(Ti02)+ 0.5 S 2 0 z -+ 1.5 H 2 0 ---+ SO=-+ 3 H+ This photod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…theoretical results. 6,7,11 In general, however (when Y" is not restricted to large values), the dependence on Y" is not a simple inverse relationship (Figure 3). Based on his experiments Showalter makes a similar observation.…”
mentioning
confidence: 97%
“…theoretical results. 6,7,11 In general, however (when Y" is not restricted to large values), the dependence on Y" is not a simple inverse relationship (Figure 3). Based on his experiments Showalter makes a similar observation.…”
mentioning
confidence: 97%
“…[14,15]. However, in the presence of ZnS particles, hydrogen can be generated with the wavelength around 350nm [6,16,17]. This suggested that the ZnS extended the useful range of the light from 290 to 350 nm.…”
Section: Resultsmentioning
confidence: 99%
“…To make more efficient use of solution with mixed sulfide and sulfite for photocatalytic hydrogen evolution, Grätzel et al further propose the concept "thiosulfate cycle" [36]. Under light illumination, S 2 O 3 2-could be disproportionated into S 2-and SO 3 2-with the assistance of TiO 2 (see specific reaction in Eqs.…”
Section: Thiosulfate Cycle For H 2 S Decompositionmentioning
confidence: 99%